A facile surfactant-free strategy to construct porous structures with hydrophobic and hydrophilic domains from polymer/water mixtures. (December 2022) - Partenope, Alessandra; Pizzetti, Fabio; Vanoli, Valeria; Casalegno, Mosè; Cingolani, Alberto; Nogueira, Liebert Parreiras; Castiglione, Franca; Haugen, Håvard J.; Rossi, Filippo
Abstract: In Pickering emulsions colloidal nanoparticles can efficiently stabilize water/oil mixtures and has been demonstrated for a wide range of applications. However the low mechanical properties of the final devices are limiting their adoption. Here we propose a strategy to use colloidal nanoparticle at hydrohobic polymer-water interface able to form biphasic, stable and porous structures during monomer polymerization. The final devices present two separate phases with different water affinities that make them extremely promising in many different fields. The strategy described present so high versatility and can be applied to different monomers and nanoparticles opening the doors to diverse applications. Graphical Abstract: ga1